Soliton pulses generation with graphene oxide saturable absorber - Harun, Sulaiman Wadi; Haris, Hazlihan (Penerbit UTHM, 2020)
Nowadays, ultrafast fiber lasers have gained tremendous interests due to their potential applications in various fields including micromachining [1], bio photonic imaging [2] and optical communication [3]. Laser can be generated by mode-locking mechanism based on either active or passive pulsing methods. Active technique synchronizes to the cavity repetition rate via an external modulator while passive technique synchronizes a within the laser resonator via an all optical nonlinear process. Due to the need for an external modulator, active pulse laser construction is rather bulky and complex in comparison to the simpler and compact construction of passive pulse laser, where its mechanism depends only on the generation of saturable absorption action. Saturable absorbers (SAs) used in passive pulse laser can be either real SAs (e.g. carbon nanotubes (CNTs), graphene) or artificial SAs (nonlinear polarization rotation (NPR)). Overall, passive technique is more cost efficient and robust compare to the active technique [4-5].